CONCEPTUAL DIFFERENCES IN REGULATING COMPULSORY SUCCESSION IN THE WORKING VERSIONS OF THE CIVIL CODES OF SERBIA AND NORTH MACEDONIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
Although the Commission for the Drafting of the Civil Code of the Republic of Serbia ceased its work inmid-2019, it can be expected that the prepared Pre-Draft of the Civil Code will serve as a solid basis forfuture work on the codification of civil law. On the other hand, in North Macedonia, the Commission forthe Drafting of the Civil Code is actively working on the preparation of the codex, particularly makingsignificant progress in the regulation of inheritance.Compulsory succession is a very significant area within the field of inheritance law, which in recent yearsand decades has undergone significant changes in European continental legal systems. These changesprimarily manifest in the expansion of the freedom of testamentary disposition of the testator, resulting innarrowing the rights of compulsory heirs. In the working versions of the civil codes of Serbia and NorthMacedonia, there are significant conceptual differences in the construction of rules related to compulsorysuccession. These differences are evident in defining the circle of compulsory heirs, the conditions theymust meet to be entitled to a compulsory share, the size of compulsory portions, the legal nature of the rightto a compulsory share, etc. The paper will point out the ideas that guided the editors of these twocodifications and discuss the substantial differences in the normative shaping of compulsory succession.Additionally, the author will share his reflections on how this significant area of inheritance law should beregulated.